ANALISIS PROSES MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KEMAMPUAN DAN PENGETAHUAN PEGAWAI DI SAKTI CELL SURABAYA - Arlisa Indriawati; Dody Yanuar Suryowibowo (Universitas Teknologi Surabaya, 2024)
This study aims to determine the management process before providing self-development programs and its considerations in improving the skills and knowledge of sales division employees, and to determine the form of self-development provided by management in improving the skills and knowledge of sales division employees. This research is a type of descriptive qualitative research. The data collection method used document recording, interview, and observation techniques. Data were analyzed using triangulation. The results of this study are employee abilities are determined by skills, knowledge matches workers with positions based on their basic knowledge, employees carry out social roles in accordance with the corporate culture, namely AKHLAK (Amanah, Competent, Harmonious, Loyal, Adaptive, and Collaborative), and employee motivation is used to realize the vision and mission of the store by producing initiatives that help in achieving organizational goals. The human resource development stage related to employee competencies is assessed at the time of recruitment and through on-the-job training.